The labor class: origin and life conditions during the industrial revolution (2020)
This essay is focused mainly in the labor class during the industrial revolution, where you want to answer questions like: In what way the labor class is consolidated as a new social class? And what implications did it have during the industrial revolution? At the moment each of these questions are answered it will be possible to get to know really if the life conditions of workers got better or industrialization made new and major problems? This way topics like: the transformation from craftsman to worker, the conformation of labor class, their arrival to the cities, the start of the need for capital, the introduction of machines into the factories and how it affected the worker with the machine arrival. But before touching those topics is necessary to make a brief description of what industrial revolution was, in order to proceed to focus in each of the items mentioned before.